When deviants talk: the role of Dark Triad traits and moral reasoning in whistleblowing - Sebastian Oelrich; Anne Chwolka (Journal of Management Control, 2024)
Abstract Whistleblowing is an effective means to uncover fraud and other misconduct in organizations. However, it is puzzling why some employees come forward despite numerous disadvantages, severe retaliation, and negative social perceptions of the whistleblower within and outside the firm. Understanding whistleblowing as an act of deviance can enrich explanations for whistleblowing in such dilemmas. Drawing on psychology literature, we look at the moderating effect of the Dark Triad (Machiavellianism, narcissism, and psychopathy), as well as moral reasoning on the factors behind the whistleblowing process. We surveyed 375 economics and business majors and found that both forms of deviance influence the decision process, making internal whistleblowing more likely. Dark Triad personalities are less influenced by adverse subjective norms and their attitude toward the consequences of whistleblowing. The negative impact of perceived retaliation on whistleblowing intention is lessened by high moral reasoning. Both types of deviations from the norm may foster whistleblowing, making it ex-post challenging to distinguish different types of whistleblowers. Importantly, we argue that specific policies, such as protection, may only serve one kind of whistleblower, disregarding the important influence of subjective norms, which may foster a more desirable type of whistleblower. Our research shows that deviant personality characteristics can counteract insufficient protection or negative cultural views on whistleblowing. These findings have direct practical implications for whistleblowing systems, corporate governance policies, and policymakers. Moreover, we contribute to an emerging stream of research that moves away from a purely pro-social view and toward a more comprehensive understanding of whistleblowing by introducing a holistic concept of whistleblowing as deviance.
Keywords: 330; Whistleblowing; Dark Triad (Machiavellianism; narcissism; psychopathy); Moral reasoning; Fraud